Spatial Orientation of Galaxies in Supercluster S[195+027+0022] - Malla, J. R.; Aryal, B.; Saurer, W. (Journal of Nepal Physical Society, 2019)
We present a study of spin vector orientation of 1198 SDSS (Sloan Digital Sky Survey) galaxies in Super cluster S[195+027+0022] having red shift 0.07 to 0.09. The databases of these galaxies are taken from SDSS (Sloan Digital Sky Survey) 7th and 9th data release. We have converted two dimensional data to three-dimensional by Godlowskian Transformation using position angle-inclination angle method. We intend to find non-random effects in the spatial orientation of galaxies in Super cluster. No preferred alignment of angular momentum vectors (spin vector) is noticed, supporting Hierarchy model of galaxy formation.